0836 Atypical presentation of Biot's breathing in a patient with Arnold Chiari Malformation II with complex sleep apnea/Sleep hypoventilation/hypoxemia not on opioid and with no history of meningitis. (25th May 2022) - Pant, Alok; Ghildiyal, Naomi; Khan, Yousaf; Baldridge, Scott; Ho, Minh; Monceaux, Brittany; Koothrezhi, Rupa; Liendo, Cesar; Chernyshev, Oleg
Abstract: Introduction: Sleep disordered breathing is very common in Arnold Chiari malformation but Biots's breathing has not been reported in these cases. Report of Cases: 3-year-old with history of Arnold Chiari II malformation with hydrocephalus (s/p VP shunt and surgical decompression), spina bifida myelomeningocele (s/p in utero repair), subglottic stenosis with prior tracheostomy and eventual decannulation presented for evaluation of sleep disordered breathing. Presenting symptoms included witnessed apneas, cyanosis, daytime sleepiness and frequent awakenings. Physical examination was largely unremarkable. Initial PSG demonstrated complex sleep apnea, with an AHI 20.6, REM AHI 57.8 per hour of sleep, ETCO2 peak of 69 cm H20 and an O2 saturation nadir of 34%, with sleep related hypoventilation/hypoxemia and Biot's breathing in the absence of opioid use and CNS infection. During titration study, Biot's breathing, complex apnea and sleep related hypoventilation/hypoxemia responded well to BiPAP ST of IPAP 18 cm H20 and EPAP 14 cm H20 BUR of 12 and oxygen of 1 L/min. She later developed intolerance to BiPAP due to high pressures and was decreased to BIPAP 13/11 cm H2O. Later the patient discontinued the use of BIPAP due to intolerance and was switched to night time O2 at 3-4 L/min. Per the parents, the patient has been maintaining her oxygen saturation in the absence of BIPAP therapy with oxygen use. Due to COVID, patient was unable to follow up but will be scheduled for a repeat PSG in the near future. She followed with Neurosurgery for Arnold Chiari II and they recommended no surgical intervention at this time due to functional VP shunt. Conclusion: This is an atypical presentation of Biot's breathing in the absence of CNS infections and opioid use in a patient with Arnold Chiari malformation II. Patient has complex sleep apnea, initially well controlled with BiPAP ST, but developed BiPAP intolerance. She is on oxygen with good control of hypoxemia in the absence of BiPAP therapy. Support (If Any):